Model disability survey: a pilot study in the North Batinah governorate - Al-Mawali, Adhra; Morsi, Magdi; Al-Kharusi, Hilal; Al-Shekaili, Waleed; Sabariego, Carla; Lee, Lindsay (Journal of Contemporary Medical Sciences, 2018)
Objective: The continuous shift to non-communicable diseases in Oman require a more consistent inclusion of functioning and disability information in health monitoring and evaluation frameworks. Oman currently relies on the census to generate data on disability which is usually very limited in scope, and provides only rough prevalence estimates of persons with specific impairments. The lack of accurate, comprehensive and up-to-date information on disability is a major obstacle for planning services and allocating resources. Thus, there was a need to conduct a comprehensive population-based survey to fill this information gap. The pilot aimed to examine the feasibility of the Arabic version of the Model Disability Survey (MDS) in the cultural context of Oman, identify potential problems with the survey, and develop strategies to deal with them before a large national implementation is launched. Methods: The MDS is the tool recommended by the World Health Organization(WHO) to collect comprehensive data about functioning and disability to quantify both the impact of health conditions or impairments as well as the impact of the environment on disability. To determine the applicability of measuring disability, a pilot study was carried out in the North Batinah governorate of Oman with a convenience sample of 288 adults aged 18 year or older in collaboration with WHO. Results: The overall disability prevalence was estimated to be 14.6% (n=42) in the MDS pilot study calculated by determining the proportion of people in the population who experience severe performance problems. The overall results corroborated that the Arabic translation of the MDS survey tool works well in the field and is suitable for a large scale implementation, after minor revisions. Conclusion: Since the results of this pilot study in Oman show that the disability measurement survey tool has been successfully tested, we recommend that the MDS be extended and implemented nationally. It should also be integrated to existing routine household surveys to allow continuous monitoring of disability in countries.